The use of microfinance services among economically active disabled people: Evidence from Uganda - Leif Atle Beisland; Roy Mersland (Journal of International Development, 2012)
This study investigates the use of microfinance services among economically active disabled people in Uganda. The findings suggest that disabled people make more use of microfinance services than previously assumed. A total of 89 per cent of the survey's respondents state that they have used at least one type of microfinance service. Informal self-help schemes are more easily accessed than formal institutional schemes, and disabled people access more savings than loans. The multivariate analysis shows that access to microfinance services is positively related to education level. In addition, deaf people generally have less access to microfinance than those in other disability categories.
Keywords: 650